Telemedicine, adherence to treatment for patients with diabetes - Vasconcelos, João Miguel; Medeiros, Aldo Cunha; de mello torres, Arthur; Filgueira Rêgo, Pedro Emanuel; Bezerra Nobre, João Victor; Nóbrega Dias, Nadson Cauã (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Introduction: Type 1 diabetes mellitus is an autoimmune disorder that involves the destruction of insulin-producing beta cells in the islets of Langerhans, a process called insulitis. Telemedicine involves the incorporation and use of modern communication systems to make the exchange of medical information between different locations more effective, providing more comprehensive medical care. Objective: To evaluate whether telemedicine is effective in increasing access and adherence to treatment for Type 1 Diabetes Mellitus. Methods: This is a systematic literature review without meta-analysis, searching for information in free databases using the search strategy ("Telemedicine" AND "Diabetes Mellitus I" AND "Patients" AND "Access to Treatment") and using the Prisma Protocol. Results: Twenty-three studies were analyzed, presenting a diversity of approaches and methodologies for the use of digital technologies, telehealth, and app- and audio-based interventions in diabetes management. Conclusion: Telemedicine has proven effective in increasing access and adherence to treatment for type 1 diabetes mellitus, contributing to glycemic control and improving patients' quality of life. However, challenges related to equity persist regarding telemedicine.